Long-Term Follow-Up of Exercise Rehabilitation Outcomes in Patients with Chronic Obstructive Pulmonary Disease - Arrowood, Tammy M. (My University, 2002)
The purpose of this study was to compare the long-term outcomes in pulmonary function, self-reported health-related quality of life, physical activity, and disability, along with functional exercise capacity in COPD patients either completing a 3-month (short-term, ST) or an 18-month (long-term, LT) exercise rehabilitation program at 58 months. Thirty-nine patients completed the follow-up study, including 12 from the ST and 27 from the LT groups. There were no significant differences between the ST and the LT groups in the adjusted means of FEV1 % predicted, (57.6 ± 3.1 versus 56.6 ± 2.1%), FEV1/FVC ratio, (51.5 ± 2.1 versus 52.1 ± 1.4%), RV/TLC ratio, (53.7 ± 4.2 versus 58.4 ± 2.8%), CRQ: dyspnea (4.9 ± 0.4 versus 5.1 ± 0.2 units), mastery (6.3 ± 0.2 versus 6.4 ± 0.1 units), emotion (5.6 ± 0.2 versus 5.7 ± 0.1 units), fatigue (4.3 ± 0.3 versus 4.7 ± 0.2 units), PASE (103.0 ± 12.2 versus 92.2 ± 8.8 units), PFQ (35.0 ± 3.8 versus 39.4 ± 2.5 units), or 6-minute walk distance, (500.7 ± 26.6 versus 517.9 ± 18.8 m) respectively, measured at the 58-months. These results showed that at 58 months there are no significant differences between the ST and the LT exercise rehabilitation groups in any of the outcome variables. Therefore, an additional 15 months of participation in an exercise rehabilitation program did not result in a difference in the level of benefits maintained at 58 months.
Keywords: exercise; long-term; Chronic Obstructive Pulmonary Disease; outcomes